Intramolecular Charge Transfer : Theory and Applications - Misra, Ramprasad; Bhattacharyya, Shankar P. (Wiley-VCH Verlag, 2018)
Bridging the gap between the multitude of advanced research articles and the knowledge newcomers to the field are looking for, this is a timely and comprehensive monograph covering the interdisciplinary topic of intramolecular charge transfer (ICT). The book not only covers the fundamentals and physico-chemical background of the ICT process, but also places a special emphasis on the latest experimental and theoretical studies that have been undertaken to understand this process and discusses key technological applications. After outlining the discovery of ICT molecules, the authors go on to discuss several important substance classes. They present the latest techniques for studying the underlying processes and show the interplay between charge transfer and the surrounding medium. Examples taken from nonlinear optics, viscosity and polarity sensors, and organic electronics testify to the vast range of applications. The result is a unique information source for experimentalists as well as theoreticians, from postgraduate students to researchers.